Synthesising synergies between CSR and BHR for corporate accountability: An integrated approach - Mallika Tamvada (International Journal of Corporate Social Responsibility (JCSR), 2023)
While an emerging literature considers Corporate Social Responsibility (CSR) as obligatory, voluntarism has dominated the scholarship and policymaking related to CSR. Almost parallel to this literature, the field of law has conceived and advanced the concept of Business and Human Rights (BHR) for addressing the human rights impacts of corporations. A new wave in the literature is exploring the relationship between these two disparate fields to bridge the corporate accountability gap. Contributing to this emerging debate, this paper develops a new CSR-BHR integrated framework that presents a unified approach towards corporate accountability. The new Framework offers a taxonomy of CSR-BHR strategies that firms can select from to prioritise their CSR-BHR activities for optimising their social contributions. It provides a new foundation for developing consistent policymaking on corporates' social obligations across the world.
Keywords: 650; Business and Human Rights; Corporate accountability; Corporate Social Responsibility